N-Octanoyl Dopamine for Donor Treatment in a Brain-death Model of Kidney and Heart Transplantation. Issue 5 (May 2015) - Spindler, Rahel S.; Schnuelle, Peter; Nickels, Lukas; Jarczyk, Jonas; Waldherr, Rüdiger; Theisinger, Sonja; Theisinger, Bastian; Klotz, Sarah; Tsagogiorgas, Charalambos; Göttmann, Uwe; Krämer, Bernhard K.; Yard, Benito A.; et al.
Abstract : Background: This study investigated the potential use of N-octanoyl dopamine (NOD) in donor management to ameliorate the damage caused by brain death and ischemia-reperfusion injury in a rat model of kidney and heart transplantation. Methods: Brain-dead Fisher rats were treated for 6 hours with either saline or saline plus NOD. Orthotopic kidney and heterotopic heart transplantation were performed in different Lewis recipient rats. The right donor kidneys were stored for biochemical analysis. Blood samples were taken from the donor and on several days after transplantation from the recipient. All grafts were harvested after 7 days. Results: There was no effect on donor heart rate and blood pressure under NOD treatment. The release of lactate dehydrogenase (LDH) during brain death was reduced in the NOD group. The right kidneys from NOD-preconditioned animals revealed diminished expression of the proinflammatory cell adhesion molecules intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1). Nevertheless, there was no difference in renal infiltration with ED1 (CD68) or major histocompatibility complex (MHC) class II–positive cells. Recipients receiving a renal allograft from NOD-treated donors had a significantly better renal function at day 1 after transplantation. Banff-grading after 7 days showed significantly reduced scores for tubulitis and vasculitis in the grafts of these recipients. In the heart allograft recipients, lower plasma LDH levels were observed. Conclusions: Donor preconditioning with NOD leads to better graft function and reduced acute rejection in untreated renal allograft recipients without displaying adverse effects on heart allografts. Abstract : Donor pretreatment of brain dead rats significantly improves transplanted graft survival and reduces rejections.